GROUP-BASED INTERVENTIONS FOR DISCIPLINE: STRENGTHENING TIME MANAGEMENT IN ISLAMIC BOARDING SCHOOL EDUCATION - Inarotul Umniyah; Nur Hermatasiyah; Aceng Akhmad Munanzdar Alkafi Billah (EDUCATIONE, 2025)
Islamic boarding schools (pesantren) play a pivotal role in Indonesian education by integrating religious values, character building, and academic achievement. However, many students struggle with time management, often leading to unfinished tasks and reduced personal growth. This study aimed to examine the implementation and impact of group guidance utilizing time management techniques to improve task-related discipline among santri at Pesantren Al-Asyhar, Central Kalimantan. Employing a descriptive qualitative approach, data were collected through participant observation, interviews, self-report questionnaires, and document analysis involving six purposively selected santri. The findings revealed that structured group guidance sessions significantly improved students’ punctuality in completing tasks, adherence to schedules, and ability to prioritize responsibilities, as reflected in both quantitative gains and qualitative testimonies from teachers and caretakers. Nevertheless, persistent challenges were observed in the area of independent schedule creation, indicating a need for ongoing mentorship. This research contributes a contextually grounded intervention model that integrates pesantren values and local culture, addressing gaps in both national and international literature. The study demonstrates practical benefits for educators, counselors, and policymakers by offering an effective strategy to foster discipline and self-management skills within pesantren and similar educational settings. For future research, it is recommended to investigate the long-term sustainability of such interventions, their scalability to other contexts, the integration of digital tools, and potential variations by gender and age.